HUBUNGAN OLAHRAGA TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI RAWAT JALAN DI RUMAH SAKIT PKU MUHAMMADIYAH SURAKARTA - Ismanto, Iksan; Rahmawati, Tuti (PROFESI || JURNAL KESEHATAN PROFESIONAL ISLAMI, 2013)
ABSTRACT Background. Hypertension can be defined as persistent blood pressure which time the systolic blood pressure above 140 mmHg and a diastolic pressure above 90 mmHg. According to data from the World Health Organization (WHO) in 2000, the world population is experiencing hypertension is 26.4 % with a ratio of men and women is equal to 26.6 % and 26.1 %. Factors that lead to hypertension that is triggering factors that can not be controlled ( heredity , age , and sex ) , which can be controlled triggering factors (obesity, smoking, lack of exercise, alcohol consumption and excessive salt consumption ). Purpose. This study aims to determine the relationship of exercise on blood pressure of hypertensive patients in the hospital outpatient PKU Muhammadiyah Surakarta. Research Method. This research uses an observational study with cross sectional approach. Exercise habits were taken to measure the frequency and duration of exercise and blood pressure were taken from medical records at the hospital last inspection. Test relationships using Spearman Rank test. Result. This study was conducted on 30 respondents, by gender characteristics that most respondents were female in the amount of 19 people (64 %) with an average self-employed work as many as 12 people 40 % , as many as 11 high school educated people (30 %) . Respondents were 17 persons (56.7 %) and exercise as much as 19 people ( 63.3 % ) did not exercise with both frequency and 20 people (66.7 %) with exercise duration is not good. 25 respondents (83.3 %) had uncontrolled blood pressure. Conclusion. There is no relationship between the frequency of exercise with blood pressure in patients with hypertension (p = 0.250 ) . There is no relationship between the duration of the exercise blood pressure in patients with hypertension (p = 0.177 ). The need for repeated studies on the same issue with other variables and the same place.